Evaluation of the Impact of Sediment Material Usage in the Upper Bili-Bili Reservoir as Fine Aggregate Substitute in Concrete Construction: Public Administration Perspective - Asnur, Moeh. Kay Muddin; Asrib, Ahmad Rifqi; Hasrul, M. Reza (PINISI Discretion Review, 2023)
Sedimentation in aquatic environments often occurs due to the presence of a high supply of sediment in that environment. Oceanographic factors, such as currents, play a significant role in the mechanism of sediment dispersion. The results of excavation processes that generate a significant amount of sediment often become unused waste. In this research, we strive to utilize the sand found in this sediment as a substitute for fine aggregates in concrete mixtures. Experimental testing methods are used to evaluate the characteristics of sediment that can be used as a substitute for fine aggregates. The research findings indicate that the sediment contains a high clay content, specifically 14.08%. We also found that concrete mixtures using 50% sediment sand from the Bili-Bili Reservoir had the highest compressive strength, reaching 17.36 MPa. However, the addition of Bili-Bili sediment sand to concrete mixtures resulted in a decrease in compressive strength. The greater the addition of Bili-Bili sediment sand, the lower the compressive strength. These findings emphasize the importance of testing materials to be used in concrete construction, especially aggregates, to meet all established requirements. By utilizing sediment as an alternative resource for fine aggregates, it can help reduce waste and consider public administration aspects in the management of sediment materials in the Bili-Bili Reservoir.